ctDNA guided management of POLE mutant GI malignancies promotes exceptional responses and prolonged survival to immunotherapy - Mahmood, Umair; Bhan, Chetan; Imber, Charles; Murphy, Jamie; Menon, Krish; Barwick, Tara D.; Amin, Zahir; Khan, Khurum (Frontiers in Immunology, 2026)
Patients with unresectable Gastrointestinal cancers (GI) including advanced colorectal cancer (CRC) and gall bladder cancer (GBC) have limited treatment options. Treatment with chemotherapy is associated with limited success resulting from therapeutic resistance. Immune checkpoint inhibitors are effective for a subset of metastatic CRC (5% with MSI-H status) and up to 30% of patients with GBC. Therefore, there is an urgent unmet need to discover new predictive biomarkers to aid patient selection for ICIs with a demonstrated clinical value in a challenging patient population. We highlight the utility of a liquid biopsy approach to aid selection of GI cancer patients harbouring rare POLE mutations for immunotherapy, leading to complete metabolic response in addition to radiologic responses and extended survival in all three patients. This study advocates for specialised multi-disciplinary teams performing shared clinical decision making to advance personalised care and improve outcomes of a subset of GI cancer patients with a poor prognosis.